2012
DOI: 10.7314/apjcp.2012.13.5.2115
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 1 Promoter-Induced JAB1 Overexpression Enhances Chemotherapeutic Sensitivity of Lung Cancer Cell Line A549 in an Anoxic Environment

Abstract: The presence of lung cancer cells in anoxic zones is a key cause od chemotherapeutic resistance. Thus, it is necessary to enhance the sensitivity of such lung cancer cells. However, loss of efficient gene therapeutic targeting and inefficient objective gene expression in the anoxic zone in lung cancer are dilemmas. In the present study, a eukaryotic expression plasmid pUC57-HRE-JAB1 driven by a hypoxia response elements promoter was constructed and introduced into lung cancer cell line A549. The cells were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The overexpression of P-gp has been shown to contribute to the development of drug resistance in numerous types of cancer cell (16). In the present study, flow cytometry was used to measure the expression levels of P-gp in the A2780 and A2780/taxol cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of P-gp has been shown to contribute to the development of drug resistance in numerous types of cancer cell (16). In the present study, flow cytometry was used to measure the expression levels of P-gp in the A2780 and A2780/taxol cells.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study demonstrated that HIF-1α is involved in the development of drug resistance in several types of cancer (16), however, its role in paclitaxel sensitivity in the A2780 cell line remains unclear. To examine the correlation between HIF-1α and paclitaxel-induced cytotoxicity, HIF-1α siRNA or a scrambled siRNA was transfected into the A2780/taxol cells, followed by treatment with various doses of paclitaxel.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis induction is an important mechanism of action of anti-cancer agents. Numerous studies have focused on the manipulation of specific genes to enhance the sensitivity of cancer cells to drugs such as the DNA-damaging agent cisplatin (28,29). High levels of Id3 have been indicated to have a role in drug resistance and disease progression and Id3 has been implicated in apoptosis in response to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cisplatin resistance is associated with multifactorial mechanisms, such as inactivation by glutathione, metallothionein, or other sulphur-containing molecules, increased repair of DNA damage and Autophagy, reduced apoptosis and intracellular drug accumulation by changing the profile of drug-influx or -efflux molecules (Song et al, 2012;Galluzzi et al, 2012;Zhang et al, 2013). Many studies, concerned with the specific gene manipulation, have provided a way to make cancer cells specifically more sensitive to cisplatin (Hu et al, 2012;Li et al, 2012;Yu et al, 2013). However, the role of Med19 in chemotherapeutic drug resistance has not yet been established.…”
Section: 875 Knockdown Of Med19 Enhances Chemo-sensitivity To Cisplamentioning
confidence: 99%